Performance tests - Reynolds, W.
This article focuses on a group of performance tests which will help you to monitor three important components of your fitness - your maximal running speed, your speed-strength (power), and your running stamina (endurance). Test A: The 30-metre sprint from a flying start Test B: 30-metre sprint bounding